Agricultural Waste Byproduct Utilization: Date Pit Powder 1h Nmr Metabolite Identification For Goat (capra Hircus) Milk Pathway Analysis - M.R.Abd Rahman; M.M. Aween; Z. Hassan; Mohd Sukri Hassan; R. Hashim; I.S. Ismail; M.S.M. Misenan; R. Ranjithkumar; K.F. Li; L.S. Wong (ScieneDirect, 2025)
Indexed by WOS/Scopus/ERA